Cultural Impact of Scholars in the Andalusian Emirate (138-442 AH / 756-1031 AD) - Alotaibi, Hussah Hindi Shuja (Journal of Al-Tamaddun, 2023)
Scholars during the Islamic ages played a significant role in the development of society, culture, and various other fields including economy, science, literature and arts etc. With the fragmentation of Abbasid caliphate, various rulers became independent and formed parallel caliphates, and adopted their own approaches towards development. Andalusian emirate is one such independent kingdom in southern Spain, which disowned its diligence to the Islamic caliphate, and adopted its own approaches to the development of the region. Scholars during this period played a significant role in transfer of technology from foreign regions, leading innovation in various sciences such as agronomy, astrology, astronomy, mathematics, arts, philosophy etc. All these events led to a significant impact on the culture and society, which are discussed and presented in this paper.